2007
DOI: 10.1007/s10108-007-9035-1
|View full text |Cite
|
Sign up to set email alerts
|

Labour segregation and immigrant and native-born wage distributions in Spain: an analysis using matched employer–employee data

Abstract: This article carries out an empirical examination of the origin of the differences between immigrant and native-born wage structures in the Spanish labour market. Especial attention is given in the analysis to the role played by occupational and workplace segregation of immigrants. Legal immigrants from developing countries exhibit lower mean wages and a more compressed wage structure than native-born workers. By contrast, immigrants from developed countries display higher mean wages and a more dispersed wage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 41 publications
2
48
0
6
Order By: Relevance
“…Indeed, Simón, Sanromá and Ramos (2008) have found that the wage gap between natives and immigrants from developed economies is favourable to the immigrant group. Therefore, it seems reasonable to expect that their economic progress would not occur or would be less important than for other groups.…”
Section: ) and In The Particular Case Of Spain By The Very Highmentioning
confidence: 99%
“…Indeed, Simón, Sanromá and Ramos (2008) have found that the wage gap between natives and immigrants from developed economies is favourable to the immigrant group. Therefore, it seems reasonable to expect that their economic progress would not occur or would be less important than for other groups.…”
Section: ) and In The Particular Case Of Spain By The Very Highmentioning
confidence: 99%
“…Recent examples of research on wage differentials and immigration, like the papers of Simón et al (2008), Canal-Domínguez and Rodríguez-Gutiérrez, or Antón et al (2010a and2010b), though documenting the issue of the earnings gap between migrants and natives not explained by human capital endowments, do not address the possibility of a double negative effect on female migrants' outcomes. In addition, there is an increasing body of research analysing the assimilation process of immigrants to the Spanish labour market, pointing out to a higher employment rate (percent of total working age population who is employed) among immigrants than among natives and finding a certain convergence in terms of employment rate and a more limited evidence of progression in terms of occupational levels (Amuedo-Dorantes and De la Rica, 2007;Alcobendas and Rodríguez-Planas, 2009) and earnings (Izquierdo et al, 2009) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…La existencia de idiomas, tecnologías u organizaciones empresariales diferentes a las del país de origen de los inmigrantes provoca que parte del capital humano adquirido por éstos no sea útil en el nuevo entorno. De hecho, los datos de la Encuesta de Estructura Salarial de 2006, mostraban que los inmigrantes al llegar a España reciben, en promedio, un salario alrededor de un 30% inferior al de un trabajador de nacionalidad española de similares características en términos de nivel educativo y experiencia profesional (Simón et al, 2008(Simón et al, y 2014. Aunque este supuesto desfase de capital laboral tampoco ha sido muy significativo ya que los puestos vacantes han sido para las mujeres, las ocupaciones de servicios más bajas (más del 60%) y para los hombres, las ocupaciones industriales y de construcción más bajas (cerca del 40%) por lo que no es que haya existido la posibilidad de aplicar los conocimientos adquiridos en el país de origen (Fernández et al, 2014).…”
Section: La Segregación Residencial Provocada Por El Mercado De Trabaunclassified